The Relationship Between Academic Stress With Academic Self-Efficacy In Vocational High School Students: Hubungan Antara Stres Akademik Dengan Efikasi Diri Akademik Pada Siswa Sekolah Menengah Kejuruan - Hasanah, Niswatun; Mariyati, Lely Ika (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the relationship between Academic Stress and Academic Self-Efficacy in Raden Paku Wringinanom. Vocational High School students. The variables contained in this study are academic stress as the independent variable and academic self-efficacy as the dependent variable. This research is a type of quantitative research with a correlational approach. The sample of this study amounted to 202 students from a total population of 479 students who were taken with the Stratification sampling technique. The results of the data analysis of this study indicate a correlation coefficient of -0.186 with a significance of 0.008, which is smaller than 0.05, meaning that there is a negative relationship between Academic Stress and Academic Self-Efficacy.